Hubungan Nilai “Lung Ultrasound Score (LUS)” dengan P/F Ratio pada Pasien Pneumonia yang Dirawat di ICU RSUP Dr Sardjito - Wibowo, Catur Prasetyo; Wisudarti, Calcarina Fitriani Retno; Jufan, Akhmad Yun (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2020)
Background: Respiratory tract disease (about 22.4%) is the frequent reason of admitting patients to the Intensive Care Unit (ICU), with 72.6% of it is caused by infection, such as pneumonia. On patient with pneumonia, there will be impairment in oxygen diffusion from alveoli to the blood flow that can affect the P/F ratio. Lung ultrasonography is directly proportional to the degree of pulmonary aeration or the ratio of air to liquid composition in the lung. Changes in pulmonary aeration can be detected accurately using pulmonary ultrasonography. Objectives: Knowing the relationship of “Lung Ultrasound Score (LUS)” with P/F ratio as a parameter to assess the degree of oxygenation in pneumonia patients treated at ICU Dr. Sardjito General Hospital. Methods: The design of this study was cross sectional study. In this study, every single sample will be examined only one time to obtain Lung Ultrasound Score (LUS) and arterial blood gas analysis (BGA) sampling to get the P/F ratio. LUS measurement was done by performing pulmonary ultrasonography at 12 predetermined examination points (6 in the left hemithorax and 6 in the right hemithorax) then scoring (0-3) per examination point, the total scoring from the 12 examination points is the result of the LUS sample. Inclusion criteria in the subjects of this study were >18 years of age, diagnosed pneumonia (score ≥6 from CPIS score), intubated with mechanical ventilation, and the candidate could be mobilized slightly right and left incline. While exclusion criteria were, patients with unstable hemodynamics (HR <60x / min or>130x / min and MAP <70mmHg or>120mmHg), pulmonary trauma, patients undergoing hemodialysis, there are contraindications to the oblique position (spinal cord injury), patients with wound dressing on the chest, and patients with morbid obese (BMI> 40). Results: There were 60 subjects in this study. Patient observation pointed that have high P/F ratio values tend to have lower Lung Ultrasound Score (LUS) values. Based on the correlation results, the value of p = 0.010 (p <0.05) with the correlation coefficient (r) = -0.332 had a negative sign which means there is a significant negative correlation between the value of Lung Ultrasound Score (LUS) with the P / F ratio with the closer relationship of the category weak (0.2 - 0.399). Conclusion: The higher the P/F ratio, the lower the LUS value in patients with pneumonia who were getting mechanical ventilation in ICU Dr. Sardjito.